Heavy gravity combined with light gravity local anesthetic in subarachnoid anesthesia for cesarean section did not reduce the incidence of intraoperative hypotension in maternal women: a prospective cohort study - Wei Qiao; Linlin Liu; Xiaoxiao Zhang; Kairui Liu; Lingzhi Wang (BMC Anesthesiology)
Abstract Background Subarachnoid anesthesia is the primary anesthetic method for elective cesarean section surgery, characterized by rapidly taking effect and reliable analgesia. However, subarachnoid anesthesia is prone to cause a high block level, resulting in a high incidence of maternal hypotension. How to reduce the incidence of maternal hypotension under subarachnoid anesthesia is a practical problem that needs to be solved urgently in clinical practice. Methods This prospective cohort study was performed at Nantong Maternal and Child Health Care Hospital in China between January and July 2023. This study compared the incidence of hypotension in pregnant women undergoing subarachnoid anesthesia during elective cesarean section in four groups, including group A (control group) with 10 mg of 10% glucose solution; Group B with 5 mg 10% glucose solution group; Group C with 4 mg 10% glucose solution group; Group D with 2 mg 10% glucose solution group. Each group was given a dose of 10 mg Ropivacaine with a concentration of 0.5% and a volume of 2 ml. The primary outcome was the incidence of maternal hypotension. The secondary outcomes were the plane of anesthesia, abdominal wall muscle relaxation degree and the incidence of adverse events. Results Data from 74 (18, A group; 26, B group; 15, C group; 15, D group) participants were analyzed. Hyperbaric combined with hypobaric local anesthetic in subarachnoid anesthesia for cesarean section did not reduce the incidence of intraoperative hypotension in pregnant women (P = 0.152). The plane of anesthesia gradually shifted from T4 to T10 as the specific gravity of ropivacaine decreased (P < 0.01). Satisfaction about abdominal wall muscle relaxation degree gradually decreased with the decrease of the specific gravity of ropivacaine (P = 0.04). And the incidence of adverse events gradually increased with the decrease of the specific gravity of ropivacaine (P = 0.027). Conclusions Hyperbaric combined with hypobaric local anesthetic in subarachnoid anesthesia for cesarean section did not reduce the incidence of intraoperative hypotension in pregnant women.